(untitled) (The Pretoria Student Law Review, 2023)
The People’s Republic of China (PRC) continues to consolidate itsposition as one of the most important trade players on the internationalmarket. The PRC has signed cooperation agreements with more than126 countries. It is also a substantial importer of raw materials,intermediate inputs, and other goods. The PRC has dealings with all 54countries on the African continent, and today the continent ranks asone of the PRC’s most important trading posts. The increasing numberof international trade and investment means naturally, that disputes ofan international nature will arise between the PRC and African parties.It is for this reason that the China-Africa Joint Arbitration Centre(CAJAC) was established. The formation of CAJAC at the instance of theForum on China – Africa Cooperation (FOCAC) is to encourage is toadminister the resolution of international disputes arising betweenChinese and African entities having their principal residence, place ofbusiness or nationality located in PRC or a country in Africa. The aim ofthis article is to examine the salient features of CAJAC which isadminister by accredited institutions which include CAJAC Beijing;CAJAC Johannesburg, CAJAC Nairobi, CAJAC OHADA, CAJAC Shanghaiand CAJAC Shenzhen.